Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\sqrt{12}+2\sqrt{27}-\sqrt{3}\right):\sqrt{3}\)
\(=\sqrt{12}:\sqrt{3}+2\sqrt{27}:\sqrt{3}-\sqrt{3}:\sqrt{3}\)
\(=\sqrt{4}+2\sqrt{9}-1\)
\(=2+6-1\)
\(=7\)
2) \(\left(4\sqrt{2}-\sqrt{8}+2\right).\sqrt{2-\sqrt{8}}\)
\(=\left(4\sqrt{2}-2\sqrt{2}+2\right).\sqrt{2-2\sqrt{2}}\)
\(=\left(2\sqrt{2}+2\right)^2.\left(\sqrt{2-2\sqrt{2}}\right)^2\)
\(=\left(8+4\right)\left(2-2\sqrt{2}\right)\)
\(=12.\left(2-2\sqrt{2}\right)\)
\(=24-24\sqrt{2}\)
\(=24\left(1-\sqrt{2}\right)\)
3) \(\sqrt{3}\left(2\sqrt{27}-\sqrt{75}+\frac{3}{2}\sqrt{12}\right)\)
\(=\sqrt{3}\left(2\sqrt{3^2.3}-\sqrt{5^2.3}+\frac{3}{2}\sqrt{2^2.3}\right)\)
\(=\sqrt{3}\left(6\sqrt{3}-5\sqrt{3}+3\sqrt{3}\right)\)
\(=\sqrt{3}.4\sqrt{3}\)
\(=12\)
1) \(\sqrt{12}\)+\(5\sqrt{3}-\sqrt{48}\)
= \(2\sqrt{3}+5\sqrt{3}-4\sqrt{3}\)
= (2+5-4).\(\sqrt{3}\)
= \(3\sqrt{3}\)
2)\(5\sqrt{5}+\sqrt{20}-3\sqrt{45}\)
= \(5\sqrt{5}+2\sqrt{5}-3.3\sqrt{5}\)
= \(5\sqrt{5}+2\sqrt{5}-9\sqrt{5}\)
= \(\left(5+2-9\right).\sqrt{5}\)
= -2\(\sqrt{2}\)
3)\(3\sqrt{32}+4\sqrt{8}-5\sqrt{18}\)
= \(3.4\sqrt{2}+4.2\sqrt{2}-5.3\sqrt{2}
\)
= 12\(\sqrt{2}\) \(+8\sqrt{2}\) \(-15\sqrt{2}\)
= \(\left(12+8-15\right).\sqrt{2}\)
= \(5\sqrt{2}\)
4)\(3\sqrt{12}-4\sqrt{27}+5\sqrt{48}\)
= \(3.2\sqrt{3}-4.3\sqrt{3}+5.4\sqrt{3}\)
= \(6\sqrt{3}-12\sqrt{3}+20\sqrt{3}\)
= \(\left(6-12+20\right).\sqrt{3}\)
= \(14\sqrt{3}\)
5)\(\sqrt{12}+\sqrt{75}-\sqrt{27}\)
= \(2\sqrt{3}+5\sqrt{3}-3\sqrt{3}\)
= \(\left(2+5-3\right).\sqrt{3}\)
= \(4\sqrt{3}\)
6) \(2\sqrt{18}-7\sqrt{2}+\sqrt{162}\)
= \(2.3\sqrt{2}-7\sqrt{2}+9\sqrt{2}\)
= 6\(\sqrt{2}-7\sqrt{2}+9\sqrt{2}\)
= \(\left(6-7+9\right).\sqrt{2}\)
= 8\(\sqrt{2}\)
7)\(3\sqrt{20}-2\sqrt{45}+4\sqrt{5}\)
= \(3.2\sqrt{5}-2.3\sqrt{5}+4\sqrt{5}\)
= \(6\sqrt{5}-6\sqrt{5}+4\sqrt{5}\)
= \(4\sqrt{5}\)
8)\(\left(\sqrt{2}+2\right).\sqrt{2}-2\sqrt{2}\)
= \(\left(\sqrt{2}\right)^2+2\sqrt{2}-2\sqrt{2}\)
= 2
a) \(\sqrt{243}-\dfrac{1}{2}\sqrt{12}-2\sqrt{75}+2\sqrt{27}=\sqrt{81.3}-\dfrac{1}{2}.2\sqrt{3}-2\sqrt{25.3}+2\sqrt{9.3}=\sqrt{81}.\sqrt{3}-\sqrt{3}-2\sqrt{25}.\sqrt{3}+2\sqrt{9}.\sqrt{3}=9\sqrt{3}-\sqrt{3}-10\sqrt{3}+6\sqrt{3}=\sqrt{3}\left(9-1-10+6\right)=4\sqrt{3}\)
b) \(\left(2+\sqrt{6}\right)\sqrt{7-4\sqrt{3}}=\left(2+\sqrt{6}\right)\sqrt{4-2\sqrt{3}.2+3}=\left(2+\sqrt{6}\right)\sqrt{\left(2-\sqrt{3}\right)^2}=\left(2+\sqrt{6}\right)\left|2-\sqrt{3}\right|=\left(2+\sqrt{6}\right)\left(2-\sqrt{3}\right)=4-2\sqrt{3}+2\sqrt{6}-3\sqrt{2}\)
c) \(\sqrt{\dfrac{\sqrt{5}}{8\sqrt{5}+3\sqrt{35}}}.\left(3\sqrt{2}+\sqrt{14}\right)=\sqrt{\dfrac{\sqrt{5}}{\sqrt{5}\left(8+3\sqrt{7}\right)}}.\left(3\sqrt{2}+\sqrt{14}\right)=\sqrt{\dfrac{1}{8+3\sqrt{7}}}.\left(3\sqrt{2}+\sqrt{14}\right)=\sqrt{\dfrac{8-3\sqrt{7}}{8^2-\left(3\sqrt{7}\right)^2}}.\sqrt{2}.\left(3+\sqrt{7}\right)=\sqrt{\dfrac{2\left(8-3\sqrt{7}\right)}{64-63}}\left(3+\sqrt{7}\right)=\sqrt{16-6\sqrt{7}}.\left(3+\sqrt{7}\right)=\sqrt{9-2.3.\sqrt{7}+7}.\left(3+\sqrt{7}\right)=\sqrt{\left(3-\sqrt{7}\right)^2}.\left(3+\sqrt{7}\right)=\left|3-\sqrt{7}\right|\left(3+\sqrt{7}\right)=\left(3-\sqrt{7}\right)\left(3+\sqrt{7}\right)=9-7=2\)
1 , \(\left(\sqrt{12}-2\sqrt{75}\right).\sqrt{3}=\sqrt{12.3}-\sqrt{300.3}=6-30=-24\)
2 , \(\sqrt{3}.\left(\sqrt{12}.\sqrt{27}-\sqrt{3}\right)=\sqrt{12.27.3}-\sqrt{3.3}=18\sqrt{3}-3\)
3 , \(\left(7\sqrt{48}+3\sqrt{27}-\sqrt{12}\right):\sqrt{3}=\left(28\sqrt{3}+9\sqrt{3}-2\sqrt{3}\right):\sqrt{3}=35\)
4 , bạn làm tương tự nhé
5 , bạn làm tương tự nhé
6 , bạn làm tương tự nhé
3) \(\sqrt{3}\left(2\sqrt{27}-\sqrt{75}+\dfrac{3}{2}\sqrt{12}\right)\)
=\(\sqrt{3}\left(2.3\sqrt{3}-5\sqrt{3}+\dfrac{3}{2}.2\sqrt{3}\right)\)
=\(\sqrt{3}\left(6\sqrt{3}-5\sqrt{3}+3\sqrt{3}\right)\)
=\(\sqrt{3}.\left(4\sqrt{3}\right)\)
=12
\(\left(2\sqrt{3}+2.3\sqrt{3}-\sqrt{3}\right):\sqrt{3}\)
=\(\left(2\sqrt{3}+6\sqrt{3}-\sqrt{3}\right):\sqrt{3}\)
=\(\left(7\sqrt{3}\right):\sqrt{3}\)
=\(7\sqrt{3}.\dfrac{1}{\sqrt{3}}\)
=7